PEMODELAN KUALITAS AIR TANAH OLEH AIR LIMBAH DOMESTIK MENGGUNAKAN ARCGIS DI DESA KERTALANGU - Gde Mahayana, Rakyan Agung (Prodi Teknik Sipil Fakultas Teknik Universitas Sebelas Maret Surakarta, 2024)
The community living in Kesiman Kertalangu Village, East Denpasar, Denpasar City, Bali, has a few open shallow wells at home. Well water is used for daily activities such as washing, washing vehicles, and watering plants. The main source of water is groundwater, which is found in rocks below the earth's surface. The availability and movement of groundwater depends on the geological conditions of the area. Groundwater that is used as a source of community life must meet good water quality, so the purpose of this study was to determine the condition of groundwater during the study. The samples used for groundwater testing were 30 wells spread across this village. The methods used were interviews with the local community, field testing of well water samples (smell and temperature tests), laboratory tests (pH, TSS, TDS, DHL and microbiology) and modeling analysis of all research data results using the ARCGIS application. The research results obtained were field tests such as odor tests and temperature tests that passed the clean water requirements because they met the standards set by the Ministry of Health. laboratory tests such as the TDS, TSS and DHL tests have met the requirements as clean water because the number of solid particles dissolved in water and gas is below the specified limits, and the amount of suspended solids in water is also below the limits. Microbiological test results showed that several points were quite polluted by E.Coli and Total Coliform bacteria caused by the distance between the well points and the septic tank in people's homes.